TO STUDY THE OUTCOME OF FISTULECTOMY WITH PRIMARY CLOSURE (CLOSED FISTULECTOMY IN TREATMENT OF FISTULA IN ANO - GAJBHIYE, VISHAL; GAJBHIYE, SACHIN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The primary objective of the study is to study the outcome of fistulectomy with primary closure (closed fistulectomy in treatment of fistula in ano, in the Department of Surgery, Ananta Institute of Medical Sciences and Research Centre, Rajsamand (Rajasthan). A pro forma containing patient demography and variables from history, clinical examination, investigations, operation undergone and outcome, is designed. Physiological data were be entered before operation and Operative data were be entered at the completion of operation. A total of 100 cases all these were operated by either of two methods, that is, open lay method (fistulomy or fistulectomy) or closure method (fistulectomy with primary closure/closed fistulectomy). Type of procedure was decided by surgeon only. Methods: A pro forma containing patient demography and variables from history, clinical examination, investigations, operation undergone and outcome, is designed. Physiological data were be entered before operation, and operative data were be entered at the completion of operation. A total of 100 cases all these were operated by either of two methods, that is, open lay method (fistulomy or fistulectomy) or closure method (fistulectomy with primary closure/closed fistulectomy). Results: Of the 80 cases treated by surgery, most of them were between 20 and 40 years of age. The age distribution of patients of two groups is compared with each other. Out of total 80 cases, (76%) were having low variety fistula and (24%) had high variety of fistula. In total patients, the maximum post-operative hospital stay was found to be 24 days and minimum 2. The average was found to be 5.88 days. In Closure method, the maximum post-operative hospital stay was found to be 4 days and minimum 2. The average was found to be 2.59 days. In open method, the maximum post-operative hospital stay was found to be 24 days and minimum 5 days. The average was found to be 9.17 days. The most common age group affected by fistula in ano found to be 31−40 years. Average found to be 34.7 years. Post-operative hospital stay was lower in patients of closed fistulectomy, with average stay of 2.59 days. Hence, from our study, we can conclude that complications and recurrence rate with closed fistulectomy are much lesser than open procedure. Even patient’s acceptance and satisfaction after closed fistulectomy is very good. Conclusion: The most common age group affected by fistula in ano found to be 31−40 years. Average found to be 34.7 years. Post-operative hospital stay was lower in patients of closed fistulectomy, with average stay of 2.59 days. Hence, from our study, we can conclude that complications and recurrence rate with closed fistulectomy are much lesser than open procedure. Even patient’s acceptance and satisfaction after closed fistulectomy is very good.